A giant arteriovenous malformation and fistula in a newborn with Parkes Weber syndrome. Case report - Auzina, Luize; Skuja, Elina; Safranovs, Toms Janis; Ozolins, Valts; Kidikas, Helmuts; Taurina, Gita; Lubaua, Inguna (Acta medica Lituanica, 2020)
Parkes Weber syndrome (PWS) is a rare congenital condition characterized by capillary cutaneous malformation, limb hypertrophy and multiple arteriovenous fistulas of the affected extremity. Another feature is a port-wine stain on the affected area. PWS is caused by genetic variations in the RAS p21 protein activator (RASA1) gene which affects the development of the vascular system. We report a case of a female neonate presenting with dyspnoea and cardiovascular insufficiency at the time of birth. The left upper extremity (LUE) and shoulder were enlarged (circumference at the midpoint was 17cm compared to 11cm on the right arm), edematous, hyperemic with a port-wine stain. Structural changes of the bones of LUE were discovered on X-ray. Echocardiography revealed right-sided volume overload, a large ductus arteriosus, a possible pathology of the aortic arch and branch arteries. Chest X-rays showed cardiomegaly. Therapy with milrinone and diuretics was started. A multislice CT angiography scan revealed arteriovenous fistula (AVF) between a. subclavia sin. and v. brachiocephalica sin, arteriovenous malformations (AVM) and a dilated a.subclavia sin. of 11 mm, as well as dilatation of other arteries of the LUE. Next generation sequencing revealed a pathogenic variation (c.2245C>T, p.Arg749*) in the RASA1 gene in the heterozygous state. Four consecutive embolizations of the AVM and AVF were performed in the first 16 months.